MANAGEMENT STRATEGY OF ISLAMIC SCHOOL (MADRASAH) PRINCIPAL IN IMPROVING TEACHER PROFESSIONALISM AT MADRASAH ALIYAH SWASTA YAYASAN MADRASAH PENDIDIKAN ISLAM IN SEI TUALANG RASO, TANJUNGBALAI - Elbiana Panjaitan (UIN Sumatera Utara Medan, 2022)
This study aims to see the development of teacher professionalism skills, strategies implemented by Madrasah (Islamic school) principals in improving teacher professionalism, and the effectiveness of management strategies used by Madrasah principals in improving teacher professionalism at MAS YMPI ST. Raso Tanjung Balai. The study follows a descriptive field method and a qualitative approach. The results of this study indicate the development of teacher professionalism at MAS YMPI ST. Raso Tanjung Balai. This can be seen that of 31 teachers, there are 30 people teachers whose education level is undergraduate (S1), and 1 teacher whose education level is still diploma. About 96.7% of teachers have met teacher competency standards. This study shows that the principal's policy on increasing the professionalism of teachers at MAS YMPI ST Raso Tanjung Balai in terms of is quite good. This can be seen from the documents made by the teacher in the form of annual programs, semester programs, syllabi, and lesson plans. The policy of the head of the Madrasa in terms of micro is quite good. This can be seen from the policies set by the school principal for teachers, such as attending educational seminars, holding discussions, conducting meetings, group studies among teachers, using laptops/ learning media during the learning process, and evaluating student learning outcomes in the middle of the semester. Regarding the effectiveness of the Madrasa principal's policy, based on the results of this study, it is considered successful but still needs to be improved in the future.